Study of the serotonin transporter (SLC6A4) and BDNF genes in French patients with non syndromic mental deficiency - Mignon Laurence; Thepault Rose-Anne; Cherpi-Antar Catherine; Védrine Sylviane; Andres Christian R; Tabagh Refaat; Dufour-Rainfray Diane; Moraine Claude; Vourc'h Patrick (BMC, 2010)
Abstract Background Mental deficiency has been linked to abnormalities in cortical neuronal network connectivity and plasticity. These mechanisms are in part under the control of two interacting signalling pathways, the serotonergic and the brain-derived neurotrophic (BDNF) pathways. The aim of the current paper is to determine whether particular alleles or genotypes of two crucial genes of these systems, the serotonin transporter gene (SLC6A4) and the brain-derived neurotrophic factor gene (BDNF), are associated with mental deficiency (MD). Methods We analyzed four functional polymorphisms (rs25531, 5-HTTLPR, VNTR, rs3813034) of the SLC6A4 gene and one functional polymorphism (Val66 Met) of the BDNF gene in 98 patients with non-syndromic mental deficiency (NS-MD) and in an ethnically matched control population of 251 individuals. Results We found no significant differences in allele and genotype frequencies in the five polymorphisms studied in the SLC6A4 and BDNF genes of NS-MD patients versus control patients. While the comparison of the patterns of linkage disequilibrium (D') in the control and NS-MD populations revealed a degree of variability it did not, however, reach significance. No significant differences in frequencies of haplotypes and genotypes for VNTR/rs3813034 and rs25531/5-HTTLPR were observed. Conclusion Altogether, results from the present study do not support a role for any of the five functional polymorphisms of SLC6A4 and BDNF genes in the aetiology of NS-RM. Moreover, they suggest no epistatic interaction in NS-MD between polymorphisms in BDNF and SLC6A4. However, we suggest that further studies on these two pathways in NS-MD remain necessary.